Constructive solution of battery swapping unit in service station for unmanned agricultural robot - Jevtuševski, Andrei; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Lillerand, Tormi; Virro, I.; Olt, Juri (My University, 2025)
The fully automated battery swapping unit is an essential part of unmanned agricultural robot service, ensuring the continuous operation of the robot by allowing the agricultural vehicle to replace its depleted battery with a fully charged one without human intervention, enabling it to continue its work cycle in the field. Thus, the battery swapping unit is part of service station systems, along with fertilizer filling, water supply, energy generation, and storage systems. This article describes a unique prototype of a battery swapping unit that safely replaces a depleted battery with a fully charged one in 223.5 seconds. The main role is played by the moving battery cart, which transports the battery between the charging and robot positions using a gripper equipped with an electric lock, attached to the actuator, and a V-belt transmission driven by an electric motor. The selection of the optimal rotation frequency of the motor is also discussed in this article.
Keywords: battery; battery swapping unit; battery charging unit; unmanned agricultural robot; service station; energy supply